"Companions": Solidarity and Race in Disability Subcultures in the United States. Issue 4 (1st November 2021) - Danforth, Scot
Abstract : The documentary Crip Camp presents a 1970s summer camp for disabled youth as a place of friendship and political dialogues that spawned the American disability rights movement. The film also represented Camp Jened as a haven of racial harmony and inclusion. Jened was not the only American micro-community of disability solidarity and political possibilities that also involved questions of racial politics. Scholars have criticized disability activists and disability studies scholars for neglecting problems of racial oppression. This historical study examines three examples of empowering disability subcultures in twentieth century America: Franklin Delano Roosevelt's Warm Springs rehabilitation resort from the mid-1920s through the mid-1940s, the Rolling Quads at the University of California, Berkeley, in the late 1960s, and Camp Interdependence in California in the 1980s. The article interrogates the racial politics of these egalitarian communities.